Keynesian capital theory: Declining interest rates and persisting profits - Peter Spahn (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
The current debate whether zero interest rates are caused by a saving glut or a liquidity glut is resolved by the distinction between the market and the natural rate, where saving affects only the latter variable, and monetary policy mainly the first. This topic is linked to a second one: the monetary determination of the rate of profit in Keynesian capital theory. Both topics merge in a critical review of Keynes's vision of the "euthanasia of the rentier". The data show however that we have not reached a state of capital satiation. The rising gap between the rate of profit and the rate of interest poses a challenge for capital theory.
urn:nbn:de:bsz:100-opus-16720
Keywords: B1; E4; E5; 330; saving vs. liquidity; zero interest rates; capital satiation